Discard Studies Wasting, Systems, and Power - Liboiron, Max (The MIT Press, 2022)
An argument that social, political, and economic systems maintain power by discarding certain people, places, and things. Discard studies is an emerging field that looks at waste and wasting broadly construed. Rather than focusing on waste and trash as the primary objects of study, discard studies looks at wider systems of waste and wasting to explore how some materials, practices, regions, and people are valued or devalued, becoming dominant or disposable. In this book, Max Liboiron and Josh Lepawsky argue that social, political, and economic systems maintain power by discarding certain people, places, and things. They show how the theories and methods of discard studies can be applied in a variety of cases, many of which do not involve waste, trash, or pollution. Liboiron and Lepawsky consider the partiality of knowledge and offer a theory of scale, exploring the myth that most waste is municipal solid waste produced by consumers; discuss peripheries, centers, and power, using content moderation as an example of how dominant systems find ways to discard; and use theories of difference to show that universalism, stereotypes, and inclusion all have politics of discard and even purification-as exemplified in "inclusive" efforts to broaden the Black Lives Matter movement. Finally, they develop a theory of change by considering "wasting well," outlining techniques, methods, and propositions for a justice-oriented discard studies that keeps power in view.